Design of a Arimbi Dance Pop-up book as an Introduction to Local Content for Elementary School Students (Jurnal Sendratasik, 2025)
This study aims to develop a prototype of an educational media in the form of a pop-up book titled Tari Arimbi as a means of introducing Sundanese local cultural content to elementary school students. The research employs a Research and Development (R&D) method based on the Borg & Gall model. The study was carried out up to the third stage, namely the design development phase. The design process involved identifying learner needs and determining appropriate visual, narrative, and educational concepts tailored to the characteristics of learners in the concrete operational stage. The results indicate that the Tari Arimbi pop-up book prototype was designed with careful consideration of graphic and visual design elements, local cultural values, and an interactive approach. This media has the potential to serve as an alternative tool for supporting cultural literacy and the preservation of traditional arts particularly dance starting from an early age.